Multidrug-resistant Pseudomonas aeruginosa is predisposed to lasR mutation through up-regulated activity of efflux pumps in non-cystic fibrosis bronchiectasis patients - Ding, Fengming; Han, Lei; Xue, Yishu; Yang, Iris Tingshiuan; Fan, Xinxin; Tang, Rong; Zhang, Chen; Zhu, Miao; Tian, Xue; Shao, Ping; Zhang, Min (Frontiers in Cellular and Infection Microbiology, 2022)
Background: Multidrug-resistant (MDR) Pseudomonas aeruginosa is a frequent opportunistic pathogen that causes significant mortality in patients with non-cystic fibrosis bronchiectasis (NCFB). Although quorum sensing (QS) system is a potential target for treatment, lasR mutants that present with QS-deficient phenotype have been frequently reported among clinical P. aeruginosa isolates. We aimed to investigate whether antibiotic resistance would select for lasR mutants during chronic P. aeruginosa lung infection, and determine the mechanism underlying the phenomenon. Methods: We prospectively evaluated episodes of chronic P. aeruginosa lung infections in NCFB patients over a 2-year period at two centers of our institution. QS phenotypic assessments and whole-genome sequencing (WGS) of P. aeruginosa isolates were performed. Evolution experiments were conducted to confirm the emergence of lasR mutants in clinical MDR P. aeruginosa cultures. Results: We analyzed episodes of P. aeruginosa infection among 97 NCFB patients, and found only prior carbapenem exposure independently predictive of the isolation of MDR P. aeruginosa strains. Compared with non-MDR isolates, MDR isolates presented with significantly QS-deficient phenotypes, which can not be complemented by exogenous addition of 3OC12-HSL. The paired isolates showed that their QS-phenotype deficiency occurred after MDR was developed. Whole-genome sequencing analysis revealed that lasR non-synonymous mutations were significantly more frequent in MDR isolates, and positive correlations of mutation frequencies were observed between genes of lasR and negative-efflux-pump-regulators (nalC and mexZ). The addition of efflux pump inhibitor PAβN could not only promote QS phenotypes of these MDR isolates, but also delay the early emergence of lasR mutants in evolution experiments. Conclusions: Our data indicated that MDR P. aeruginosa was predisposed to lasR mutation through up-regulated activity of efflux pumps. These findings suggest anti-QS therapy combined with efflux pump inhibitors might be a potential strategy for NCFB patients in the challenge of MDR P. aeruginosa infections.